Analysis of the potential value of cultural ecosystem services: A case study of Busan City, Republic of Korea - Lee, Dong-Kyu (Ecosystem services, 2024)
Although the importance of ecosystem services (ES) as a result of urbanization continues to be emphasized, their economic value to cities as a whole has not been widely explored. This study aimed to provide basic data to respond to the continuously increasing demand for ESs by analyzing the potential value of cultural ecosystem services (CESs). These services are among the most important ESs and represent the most intimate interactions between humans and nature. The ongoing Busan Eco Delta City development was selected as the study subject. Using the concept of compensating surplus as a theoretical framework, the benefit derived from CESs by local citizens was determined. A questionnaire-based survey was conducted on the willingness to pay and its influence on CESs. Results from the 1,477 survey responses showed that the willingness to pay for CESs was affected by the offer amount, age, place of residence, willingness to visit, and environmental organization membership. The average value ascribed to CESs was KRW 9,044, based on a dichotomous-choice response logit model. Among the CESs, the existence CES had the strongest influence on willingness to pay, indicating that the natural resources of the urban ecosystem were of the highest value to the residents. This study presents a clear approach to estimating the potential value of cultural services derived from the urban ecosystem and provides reference data for decision-making processes such as planning and policy establishment.